1994
DOI: 10.3109/02844319409071195
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Avascular Necrosis of the Scaphoid

Abstract: A 30 year old woman presented with pain in her right wrist a year after operation for de Quervain's tenosynovitis. Magnetic resonance imaging showed avascular necrosis of the scaphoid without loss of volume. She was instructed to wear a brace on her wrist while working. A year later she was free of symptoms but the scan was unchanged. Avascular necrosis of the scaphoid not associated with injury is extremely rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, in a number of cases no obvious cause is identified (Guelpa et al 1980, Ekerot and Eiken 1981, Allen 1983, De Smet et al 1993, Herbert and Lanzetta 1993, Dossing and Boe 1994. In recent years, there has been an increase in the number of reports of idiopathic avascular necrosis of the scaphoid, perhaps reflecting the increased awareness of clinicians regarding the existence of this rather uncommon condition.…”
Section: Discussionmentioning
confidence: 96%
“…However, in a number of cases no obvious cause is identified (Guelpa et al 1980, Ekerot and Eiken 1981, Allen 1983, De Smet et al 1993, Herbert and Lanzetta 1993, Dossing and Boe 1994. In recent years, there has been an increase in the number of reports of idiopathic avascular necrosis of the scaphoid, perhaps reflecting the increased awareness of clinicians regarding the existence of this rather uncommon condition.…”
Section: Discussionmentioning
confidence: 96%
“…In parallel with these diverse definitions, a wide-ranging aetiology has been described. Preiser’s disease has been used synonymously for idiopathic avascular necrosis, meaning avascular necrosis without clear aetiology (Allen et al, 1983; Alnot et al, 1990; Dossing et al, 1994; Ekerot et al, 1981; Ferlic et al, 1989; Gupta et al,1992; Herbert et al, 1994; Jensen et al, 1995; Lauder et al, 2006; Martini et al, 1995; Parkinson et al, 1991; Zadeh et al, 1996; Zeng et al, 2001). Several nontraumatic causes have been described including steroid use (Chang et al, 1993; Kawai et al, 1983; Virik et al, 2001), systemic disease (Aptekar et al, 1974; Tate et al, 2000), chemotherapy (Chang et al, 1993; Harper et al, 1984), and smoking (Chang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Scaphoid fractures are less common in the immature scaphoid (Green et al, 1984;Larson et al, 1987), and ischaemia and avascular necrosis is more widely reported in adults (Dossing and Boe, 1994;Ferlic and Morin, 1989;Herbert and Lanzetta, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Acute ischaemia of the scaphoid is rare in the absence of a fracture, though numerous cases of avascular necrosis have been reported, both in the presence and absence of trauma (Dossing and Boe, 1994;Ferlic and Morin, 1989;Herbert and Lanzetta, 1993;Jensen and Leicht, 1995;Larson et al, 1987). Avascular necrosis is rare in children, but has been described in a 5-year-old boy following a fracture (Larson et al, 1987), and in a 10year-old with no history of significant trauma (Jensen and Leicht, 1995).…”
Section: Introductionmentioning
confidence: 99%